<span>5-6n=2n+5 , 5 cancels out
-6n -2n = 0
-8n = 0
n =0</span>
Answer:
We want to find:
![\lim_{n \to \infty} \frac{\sqrt[n]{n!} }{n}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B%5Csqrt%5Bn%5D%7Bn%21%7D%20%7D%7Bn%7D)
Here we can use Stirling's approximation, which says that for large values of n, we get:
![n! = \sqrt{2*\pi*n} *(\frac{n}{e} )^n](https://tex.z-dn.net/?f=n%21%20%3D%20%5Csqrt%7B2%2A%5Cpi%2An%7D%20%2A%28%5Cfrac%7Bn%7D%7Be%7D%20%29%5En)
Because here we are taking the limit when n tends to infinity, we can use this approximation.
Then we get.
![\lim_{n \to \infty} \frac{\sqrt[n]{n!} }{n} = \lim_{n \to \infty} \frac{\sqrt[n]{\sqrt{2*\pi*n} *(\frac{n}{e} )^n} }{n} = \lim_{n \to \infty} \frac{n}{e*n} *\sqrt[2*n]{2*\pi*n}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B%5Csqrt%5Bn%5D%7Bn%21%7D%20%7D%7Bn%7D%20%3D%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B%5Csqrt%5Bn%5D%7B%5Csqrt%7B2%2A%5Cpi%2An%7D%20%2A%28%5Cfrac%7Bn%7D%7Be%7D%20%29%5En%7D%20%7D%7Bn%7D%20%3D%20%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7Bn%7D%7Be%2An%7D%20%2A%5Csqrt%5B2%2An%5D%7B2%2A%5Cpi%2An%7D)
Now we can just simplify this, so we get:
![\lim_{n \to \infty} \frac{1}{e} *\sqrt[2*n]{2*\pi*n} \\](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B1%7D%7Be%7D%20%2A%5Csqrt%5B2%2An%5D%7B2%2A%5Cpi%2An%7D%20%5C%5C)
And we can rewrite it as:
![\lim_{n \to \infty} \frac{1}{e} *(2*\pi*n)^{1/2n}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B1%7D%7Be%7D%20%2A%282%2A%5Cpi%2An%29%5E%7B1%2F2n%7D)
The important part here is the exponent, as n tends to infinite, the exponent tends to zero.
Thus:
![\lim_{n \to \infty} \frac{1}{e} *(2*\pi*n)^{1/2n} = \frac{1}{e}*1 = \frac{1}{e}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B1%7D%7Be%7D%20%2A%282%2A%5Cpi%2An%29%5E%7B1%2F2n%7D%20%3D%20%5Cfrac%7B1%7D%7Be%7D%2A1%20%3D%20%5Cfrac%7B1%7D%7Be%7D)
Answer:
4400 yards
Step-by-step explanation:
Convert miles into yards.
Step-by-step explanation:
Given bi-quadratic equation is:
Substituting
given bi-quadratic equation reduces in the form of following quadratic equation:
Let us factorize the above quadratic equation:
Since square root of a negative number cannot be found, so:
![CASE\: (2)\:\\When\: a =5 \implies x^2 =5\\\therefore x=\pm \sqrt{5}\\](https://tex.z-dn.net/?f=CASE%5C%3A%20%282%29%5C%3A%5C%5C%3C%2Fp%3E%3Cp%3EWhen%5C%3A%20a%20%3D5%20%5Cimplies%20x%5E2%20%3D5%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20x%3D%5Cpm%20%5Csqrt%7B5%7D%5C%5C%3C%2Fp%3E%3Cp%3E)
Step-by-step explanation:
1. You already got the first step, where D is the midpoint of AC and AB is congruent to BC, since it's given.
2. AD will be congruent to DC, via the definition of a midpoint (a midpoint is the middle point of a line segment, and it splits the segment into two congruent parts)
3. BD is equal to BD, via reflexive property. ( It's a shared side between the two triangles)
4. that means that ΔADB ≅ΔCDB via SSS rule.
5. ∠ABD ≅∠CDB by CPCTC (corresponding parts of congruent triangles are congruent)
Hope this helps! :)